C++ Quick syntax reference - Olsson, Mikael (Apress Imprint: Apress, 2013)
The C++ Quick Syntax Reference is a condensed code and syntax reference to the C++ programming language. It presents the essential C++ syntax in a well-organized format that can be used as a handy reference. You won't find any technical jargon, bloated samples, drawn out history lessons, or witty stories in this book. What you will find is a language reference that is concise, to the point and highly accessible. The book is packed with useful information and is a must-have for any C++ programmer. In the C++ Quick Syntax Reference, you will find: A concise reference to the C++ language syntax. Short, simple, and focused code examples. A well laid out table of contents and a comprehensive index allowing easy review.